The Catholic Church in Philipine politics - Ofreneo, Rosalinda Pineda (Journal of contemporary Asia, 1987)
The paper outlines in very broad strokes the role the Catholic Church has played in Philippine politics from the Spanish conquest to the present, but concentrating on the past decade, especially on the events in 1986. The launching of the Partido Kommunista ng Pilipinas (PKP) in the 1930s and anti-communism and intolerance of certain Church elements, particularly of the Jesuits. The Catholic Church before and after the February 1986 "revolution". Its attitudes to the Aquino Government. (DÜI-Sen)